Effect of shear localisation on yield surface for porous metals containing ellipsoidal voids. (1st October 2021) - Kumar, Suranjit; Samal, M.K.; Singh, P.K.; Chattopadhyay, J.
Abstract: Diffused and localised plasticity in a narrow band between the pre-existing micro-voids are the dominant modes of deformation in a ductile material. In this paper, a yield function is presented for porous metallic materials accounting for these two modes of deformation. The model has been proposed by modifying Madou and Leblond's model taking into account the effect of shear localisation between the inter voids ligaments on evolution of yield surface. The proposed model gives a smooth yield locus and captures the competition between defused plasticity and shear localisation as a function of void shape. The results of proposed model have been extensively validated with numerically evaluated yield locus using the finite element based limit analysis for a wide range of ellipsoidal void geometries. It has been shown that the model accurately predicts the effect of shear localisation on the yield surface. Highlights: Diffused and localised plasticity are predominant modes of deformation in ductile materials. A yield function is proposed for porous metal plasticity. It captures the competition between these two modes of deformation. It also accounts for the void shape effect in the generation of yield locus. It has been numerically validated over a wide range of ellipsoidal void geometries.